Copper powder, copper paste containing same, and method for producing conductive film

By using specific combinations of copper particles A and B, as well as surface treatment technology, the problems of conductive film continuity, density and low-temperature sintering are solved, and efficient conductive film manufacturing is achieved.

CN119816388APending Publication Date: 2025-04-11MITSUI MINING & SMELTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063345.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to ensure both continuity, density and low-temperature sintering properties of the conductive film, especially when mixing spherical and flat copper particles.

Method used

A copper powder containing specific copper particles A and copper particles B is used, wherein copper particles A have an average particle size of 0.1 μm to 0.6 μm and covers the copper salt of aliphatic organic acids on the surface, and copper particles B have a specific microcrystal size ratio and shape. Through the combination and surface treatment of these copper particles, an efficient conductive film is formed.

Benefits of technology

High continuity and density of the conductive film are achieved, and the sintering temperature is reduced, which improves the low-temperature sintering and conductive properties of copper particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005294003440000241
    Figure BDA0005294003440000241
  • Figure BDA0005294003440000281
    Figure BDA0005294003440000281
  • Figure BDA0005294003440000311
    Figure BDA0005294003440000311
Patent Text Reader

Abstract

The copper powder contains the following copper particles A and copper particles B, with respect to the total of the copper particles A and the copper particles B, the content ratio of the copper particles A is 60% by mass or more and 99% by mass or less, and the content ratio of the copper particles B is 1% by mass or more and 40% by mass or less. (Copper particle A) Each of the copper particles is provided with a core particle containing copper and a coating layer that covers the surface of the core particle, and the coating layer is formed from a copper salt of an aliphatic organic acid and has a primary particle diameter of 0.1-0.6 [mu] m (inclusive). (copper particle B) for the copper particles, the ratio (S1 / B) of a first crystallite size (S1) to a BET diameter (B) as determined from the half-value amplitude of a peak derived from the (111) plane of copper in X-ray diffraction measurement is 0.23 or less, the ratio (S1 / S2) of S1 to a second crystallite size (S2) as determined from the half-value amplitude of a peak derived from the (220) plane is 1.35 or less, and the primary particle diameter is 0.1-2.0 [mu] m (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to copper powder and copper paste containing the same. In addition, the present invention also relates to a method for producing a conductive film. Background Art

[0002] Copper is widely used as a conductive material in industry because it is a highly conductive metal and a highly versatile material. For example, copper powder, which is an aggregate of copper particles, is widely used as a raw material for various electronic components such as external electrodes and internal electrodes of multilayer ceramic capacitors (hereinafter also referred to as "MLCC") and wiring on various substrates.

[0003] As one of such copper powders, the present applicant has previously proposed a technology involving spherical copper particles, wherein the average particle size of the primary particles of the spherical copper particles is greater than or equal to 0.1 μm and less than or equal to 0.6 μm, and a surface treatment agent is applied to the particle surface (see Patent Document 1). According to this technology, there is an advantage that the low-temperature sintering property of the copper particles becomes good.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-168878 Summary of the invention

[0007] However, when a paste is prepared using spherical copper particles and various conductive films are produced from the paste, it may be difficult to ensure the continuity of the conductive film due to the particle shape.

[0008] On the other hand, flat copper particles are also known as copper particles. However, when a paste is prepared using flat copper particles and various conductive films are produced from the paste, it may be difficult to increase the density of the conductive film due to the particle shape.

[0009] Therefore, currently, in order to make up for each other's shortcomings, spherical copper particles and flat copper particles are often mixed for use. However, recently, in addition to the continuity and density of the conductive film, the low-temperature sintering property of the copper particles when manufacturing the conductive film is also required. When the spherical copper particles and the flat copper particles are simply mixed for use, the low-temperature sintering property of the mixed copper particles is not improved.

[0010] Therefore, an object of the present invention is to provide a copper powder which can produce a conductive film with high continuity and density and has a low sintering temperature.

[0011] The present invention provides a copper powder, which comprises the following copper particles A and copper particles B, wherein:

[0012] The content ratio of copper particles A relative to the total of copper particles A and copper particles B is 60 mass % or more and 99 mass % or less, and the content ratio of copper particles B is 1 mass % or more and 40 mass % or less.

[0013] 〔Copper particles A〕

[0014] The copper particle includes a core particle containing copper and a covering layer covering a surface of the core particle.

[0015] The above-mentioned coating layer is formed of a copper salt of an aliphatic organic acid.

[0016] The primary particle size is 0.1 μm or more and 0.6 μm or less.

[0017] 〔Copper particles B〕

[0018] For the copper particles, the ratio (S1 / B) of the first crystallite size S1 obtained by the Scherrer equation from the half-value width of the peak originating from the (111) plane of copper in X-ray diffraction measurement to the BET diameter B calculated from the BET specific surface area is 0.23 or less,

[0019] The ratio (S1 / S2) of the first crystallite size S1 to the second crystallite size S2 obtained by the Scherrer equation from the half-value width of the peak derived from the (220) plane of copper in X-ray diffraction measurement is 1.35 or less,

[0020] The primary particle size is 0.1 μm or more and 2.0 μm or less. DETAILED DESCRIPTION

[0021] The present invention will be described below based on preferred embodiments thereof. The copper powder of the present invention includes copper particles A and copper particles B described below.

[0022] 〔Copper particles A〕

[0023] The copper particle includes a core particle containing copper and a covering layer covering a surface of the core particle.

[0024] The above-mentioned coating layer is formed of a copper salt of an aliphatic organic acid.

[0025] The primary particle size is 0.1 μm or more and 0.6 μm or less.

[0026] 〔Copper particles B〕

[0027] For the copper particles, the ratio (S1 / B) of the first crystallite size S1 obtained by the Scherrer equation from the half-value width of the peak originating from the (111) plane of copper in X-ray diffraction measurement to the BET diameter B calculated from the BET specific surface area is 0.23 or less,

[0028] The ratio (S1 / S2) of the first crystallite size S1 to the second crystallite size S2 obtained by the Scherrer equation from the half-value width of the peak derived from the (220) plane of copper in X-ray diffraction measurement is 1.35 or less,

[0029] The primary particle size is 0.1 μm or more and 2.0 μm or less. However, copper particles corresponding to copper particles A are excluded.

[0030] As a result of intensive research, the present inventors surprisingly found that the copper powder containing the copper particles A and B has a low sintering temperature and that a conductive film produced from a copper paste containing the copper powder has high continuity and density.

[0031] From the viewpoint of further enhancing the above-mentioned effects, the copper particle A preferably has a spherical shape. On the other hand, the copper particle B preferably has a flat shape.

[0032] From the viewpoint of improving the sinterability of the copper powder of the present invention at low temperature and improving the conductivity of the conductive film obtained by sintering the particles, the average image analysis diameter of the primary particles of the copper particles A is preferably 0.1 μm or more and 0.6 μm or less, more preferably 0.12 μm or more and 0.4 μm or less, and further preferably 0.15 μm or more and 0.3 μm or less. The primary particle refers to an object that is determined from the geometric form of the outer shape and is confirmed as the smallest unit of the particle.

[0033] From the same viewpoint, the average image analysis diameter of the primary particles of the copper particles B is preferably 0.1 μm or more and 2.0 μm or less, more preferably 0.15 μm or more and 1.0 μm or less, and further preferably 0.2 μm or more and 0.6 μm or less.

[0034] In addition, the particle size of the copper particles A calculated from the BET specific surface area (hereinafter also referred to as BET diameter A) is preferably 0.1 μm or more and 0.6 μm or less, more preferably 0.12 μm or more and 0.4 μm or less, and further preferably 0.15 μm or more and 0.3 μm or less. By making the BET diameter A into such a range, the thermal conductivity of the copper powder of the present invention can be improved, and the sintering temperature can be effectively reduced.

[0035] From the same point of view, the particle size of the copper particles B calculated from the BET specific surface area (hereinafter also referred to as BET diameter B) is preferably 0.1 μm or more and 2.0 μm or less, more preferably 0.15 μm or more and 1.0 μm or less, and further preferably 0.2 μm or more and 0.6 μm or less. By making the BET diameter B into such a range, the thermal conductivity of the copper powder of the present invention can be improved, and the sintering temperature can be effectively reduced.

[0036] In this specification, the BET diameter B is also referred to as the primary particle diameter of the copper particles B.

[0037] The average image analysis diameter of the primary particles of copper particles A and B can be obtained by, for example, observing the copper particles at a magnification of 10,000 times or 30,000 times using a scanning electron microscope (JSM-6330F manufactured by JEOL Ltd.), measuring the maximum Feret diameter in the horizontal direction for 200 particles in the field of view, and calculating the volume average particle diameter converted into spheres from these measured values.

[0038] In this specification, the average image analysis diameter of the primary particles of the copper particles A calculated in this way is also referred to as the primary particle size of the copper particles A.

[0039] The BET diameters A and B calculated from the BET specific surface area can be measured based on the BET method according to the following conditions. Specifically, the measurement can be performed by nitrogen adsorption using "Macsorb" manufactured by MOUNTECH Co., Ltd. The amount of the measured powder is set to 0.2 g, and the pre-degassing conditions are set to 30 minutes at 80°C under vacuum. Then, the BET diameters A and B are calculated from the measured BET specific surface area by the following formula (I).

[0040] In formula (I), d is the BET diameter A or B [μm], A BET The specific surface area [m 2 / g], ρ is the density of copper [g / cm 3 ].

[0041] d=6 / (A BET ×ρ)(I)

[0042] Hereinafter, preferred embodiments of the copper particles A and B will be described in detail.

[0043] <Preferred Embodiment of Copper Particle A>

[0044] Copper particles A are copper particles to which a surface treatment agent containing a copper salt of an aliphatic organic acid is applied on the surface of the particles. Thus, a covering layer formed by the surface treatment agent is formed in a manner that continuously or discontinuously covers the surface of the core particles containing copper. The surface treatment agent is used to suppress both oxidation of copper and aggregation of particles.

[0045] Furthermore, the core particles preferably contain only copper and the remainder of inevitable impurities.

[0046] As described above, the surface treatment agent used in the present invention contains a copper salt of an aliphatic organic acid.

[0047] In the technical field, in order to take into account both the inhibition of copper oxidation in copper particles and the inhibition of agglomeration between particles, surface treatment agents such as fatty acids or fatty acid amines are used. However, such treatment agents sometimes have a high decomposition temperature and cannot be fully removed during the sintering of copper particles. As a result, the sintering start temperature sometimes rises or the resistance of the conductive film obtained after the sintering of copper particles becomes higher. In order to solve this problem, the inventors conducted in-depth research and found that by using a copper salt of an aliphatic organic acid as a surface treatment agent, both the oxidation of copper and the agglomeration of particles can be suppressed, and the sintering start temperature can be reduced. As a result, the low-temperature sintering properties of particles can be improved and the resistance of the conductive film obtained after sintering can be reduced.

[0048] From the viewpoint of lowering the sintering temperature of the copper powder of the present invention and having both copper oxidation inhibition and particle aggregation inhibition, the carbon number of the aliphatic organic acid constituting the copper salt of an aliphatic organic acid is preferably 6 or more and 18 or less, more preferably 8 or more and 18 or less, further preferably 10 or more and 18 or less, and further preferably 12 or more and 18 or less. As such an aliphatic organic acid, for example, a linear or branched, saturated or unsaturated carboxylic acid, or a sulfonic acid having a linear or branched, saturated or unsaturated hydrocarbon group, etc., can be cited, preferably a linear, saturated or unsaturated carboxylic acid. In addition, the valence of copper in the copper salt of an aliphatic organic acid is monovalent or divalent, preferably divalent.

[0049] Specific examples of the carboxylic acid include citric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, palmitic acid, oleic acid, and stearic acid. Lauric acid, oleic acid, and stearic acid are preferred, and lauric acid and stearic acid are more preferred.

[0050] Specific examples of the sulfonic acid include hexanesulfonic acid, heptanesulfonic acid, octanesulfonic acid, nonanesulfonic acid, decanesulfonic acid, laurelsulfonic acid, palmitic acid, olesulfonic acid, stearylsulfonic acid, etc. These aliphatic organic acids may be used alone or in combination of two or more.

[0051] The surface treatment agent can be applied to the particle surface by, for example, contacting the obtained core particles with a copper salt of an aliphatic organic acid as a surface treatment agent in a process after manufacturing the core particles containing copper. The amount of the surface treatment agent applied is expressed as the proportion (mass %) of the surface treatment agent as a whole in the copper particles A in the state to which the surface treatment agent is applied, and is preferably set to 0.2 mass % or more and 2.0 mass % or less in terms of carbon atoms, and is further preferably set to 0.3 mass % or more and 1.0 mass % or less. By utilizing the removal of the oxide film on the surface of the copper particles brought by the surface treatment agent and the effect brought by the eutectic solution within such a range, the melting temperature of the copper particles can be lowered, and as a result, the sintering temperature can be reduced.

[0052] The ratio (mass %) of the surface treatment agent applied to the surface of the copper particles A can be measured as follows. The ratio of the surface treatment agent is calculated by heating 0.5 g of copper powder, which is an aggregate of copper particles A to which the surface treatment agent is applied, in an oxygen flow using a carbon / sulfur analyzer (manufactured by Horiba, Ltd., EMIA-320V), decomposing the carbon component in the copper powder into CO or CO2, and quantifying the amount thereof.

[0053] The qualitative and quantitative analysis of the surface treatment agent can be performed by, for example, nuclear magnetic resonance (NMR), Raman spectroscopy, infrared spectroscopy, liquid chromatography, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc., alone or in combination.

[0054] Copper particle A is a copper particle having a coating layer formed on the surface of the core particle using a copper salt of an aliphatic organic acid as a surface treatment agent. Whether the coating layer is formed using a copper salt of an aliphatic organic acid can be determined, for example, by the following method. Specifically, the copper particle A is diluted with KBr so that the mass of the copper particle A becomes 5 mass %, and the measurement sample mixed in a mortar is measured by a diffuse reflection method with a resolution of 4 cm using an infrared spectrophotometer (model: FT-IR4600) manufactured by JASCO Corporation. -1 The measurement was performed under the conditions of 128 accumulation times, and the vertical axis was the value obtained by Kubelka-Munk conversion of absorbance, and the horizontal axis was the wave number (500-4000cm -1 ) chart (spectrum). At this time, if the infrared absorption peak is at 1504cm -1 Above and 1514cm -1 The following ranges were observed, and at 1584 cm -1 Over 1596cm -1 If no ions are observed within the following range, it can be determined that the coating layer is formed using a copper salt of an aliphatic organic acid. That is, the copper particles A preferably have a luminescence intensity of 1504 cm-1 and a wavelength of 1504 cm-1 when measured by infrared spectroscopy. -1 Above and 1514cm -1 Infrared absorption peaks were observed in the following ranges: 1584 cm -1 Over 1596cm -1 No infrared absorption peak was observed in the following range.

[0055] "Having an infrared absorption peak" is defined as follows. First, -1 Above and 2940cm -1 The normalized IR spectral data were differentiated twice at the maximum of the peaks observed within the range below 1500 cm -1Over 1600cm -1 The waveforms are separated based on the zero-up cut method within the following range. Next, the arithmetic mean is calculated from the absolute value of the amplitude from the baseline (zero) in each waveform after waveform separation. Then, when the absolute value of the peak height is greater than half of the arithmetic mean, it is set as "having an infrared absorption peak".

[0056] It should be noted that in the case of copper particles using fatty acids or aliphatic amines as the surface treatment agent, due to the -1 Over 1596cm -1 Since an infrared absorption peak is detected in the following range, it can be distinguished from copper particle A in this point.

[0057] The reason why copper particles capable of suppressing both copper oxidation and aggregation of particles and lowering the sintering temperature of the copper powder of the present invention can be obtained by using a copper salt of an aliphatic organic acid is not clear, but the present inventors presume as follows.

[0058] As described above, the copper particles of the present invention and the copper particles using a fatty acid or an aliphatic amine as a surface treatment agent differ in the presence or absence of an infrared absorption peak at a specific wave number.

[0059] Infrared spectroscopy is based on the principle of measuring the absorption of light energy equivalent to the kinetic energy of bonds in molecules by irradiating infrared rays to the substance or molecule to be measured. Generally speaking, when infrared absorption is observed in infrared spectroscopy, it means that some kind of bond exists in the molecule. In particular, when infrared absorption is observed at a high wave number position, since the infrared energy at a high wave number is high, it can be said that there is a bond with a large bonding energy in the molecule.

[0060] When copper particles A are compared with copper particles using fatty acids or aliphatic amines as surface treatment agents, since both particles have a surface area of ​​1504 cm -1 Above and 1514cm -1 Infrared absorption was observed in the low wave number region within the following range, and therefore it is presumed that absorption in this region means that a coating layer is bonded to the surface of the core particle. Therefore, it is considered that both oxidation of copper of the core particle and aggregation of particles can be suppressed.

[0061] On the other hand, if we focus on 1584cm -1 Over 1596cm -1In the high wave number region of the following range, the infrared absorption observed in the above high wave number region is not observed in copper particle A, while infrared absorption is observed in the above high wave number region for copper particles using fatty acids or aliphatic amines as surface treatment agents. That is, it means that the copper particles of the present invention have fewer bonds with large bonding energy in the molecule compared with copper particles using fatty acids or aliphatic amines as surface treatment agents. This is because it is believed that the bond between the surface treatment agent and the core particle becomes relatively weak in the copper particles of the present invention, so it is believed that the surface treatment agent becomes easy to detach at low temperatures, and the sintering of the particles can be achieved at low temperatures.

[0062] Based on the above reasons, it is considered that by applying a surface treatment agent containing a copper salt of an aliphatic organic acid to the surface of the copper particles A, both oxidation of copper and aggregation of particles can be suppressed, and a decrease in the sintering temperature can be achieved.

[0063] Furthermore, in order to identify the type of aliphatic organic acid constituting the copper salt of an aliphatic organic acid, the copper particles A can be analyzed by, for example, TOF-SIMS.

[0064] From the viewpoint of further lowering the sintering temperature of the copper powder of the present invention, in the thermogravimetric analysis when the copper particles A are heated from 25°C to 1000°C, the temperature at which the ratio of the mass reduction value to the mass reduction value at 500°C becomes 10% is preferably 150°C to 220°C, and more preferably 180°C to 220°C.

[0065] The above-mentioned thermogravimetric analysis can be performed, for example, by the following method. That is, using TG-DTA2000SA manufactured by Bruker AXS, the sample to be measured is set to 50 mg, and the mass reduction rate when heated from 25°C to 1000°C is measured. The atmosphere is set to nitrogen, and the heating rate is set to 10°C / min. The lower the temperature at which the mass reduction rate becomes a predetermined ratio, the lower the temperature at which the aliphatic organic acid forming the coating layer can be removed, and thus becomes a measure of the low-temperature sintering property of the copper particle A.

[0066] As described above, the shape of the copper particle A is preferably spherical. In order to obtain spherical copper particles A, for example, the shape of the core particle can be set to be spherical. It should be noted that the particles are spherical, which means that the circularity coefficient measured by the following method is preferably 0.85 or more, and more preferably 0.90 or more. The circularity coefficient is calculated by the following method. Take a scanning electron microscope image of the metal particles, and randomly select 1000 copper particles that do not overlap with each other. When the area of ​​the two-dimensional projection image of the particle is set to S and the perimeter is set to L, 4πS / L 2The circularity coefficient of the particle is calculated by the formula. The arithmetic mean of the circularity coefficients of the particles is taken as the circularity coefficient mentioned above. When the two-dimensional projection image of the particle is a perfect circle, the circularity coefficient of the particle becomes 1.

[0067] <Preferred Embodiment of Copper Particle B>

[0068] The crystallite size in a specific crystal plane calculated by X-ray diffraction measurement of the copper particle B has a prescribed relationship. Specifically, when the particle size calculated by the BET specific surface area is set as the BET diameter B, and the crystallite size obtained by the Scherrer formula from the diffraction peak derived from the (111) plane of copper in the X-ray diffraction measurement is set as the first crystallite size S1, the ratio (S1 / B) of the first crystallite size S1 to the BET diameter B is preferably 0.23 or less, more preferably 0.02 or more and 0.23 or less, and further preferably 0.05 or more and 0.23 or less.

[0069] The diffraction peak originating from the (111) surface of copper is a peak with the maximum height of the X-ray diffraction pattern obtained by X-ray diffraction measurement of copper particle B. It is therefore believed that the first crystallite size is larger than the crystallite size calculated from the diffraction peaks originating from other crystal planes, and also represents representative crystallinity. Therefore, it is speculated that by forming a structure in which the first crystallite size S1 is smaller than the BET diameter B, there are more crystal grain boundaries in one particle. As a result, by applying thermal energy when heating the particles, the crystallite interface tends to become unstable and atomic diffusion becomes active, which can improve the fusibility of particles at low temperatures and reduce the sintering temperature.

[0070] Such copper particles can be obtained, for example, by the production method described below.

[0071] The first crystallite size S1 of the copper particle B is preferably 10 nm or more and 80 nm or less, more preferably 20 nm or more and 75 nm or less, and further preferably 25 nm or more and 70 nm or less. When the crystallite size S1 is within such a range, more crystal grain boundaries are easily formed in one particle, the fusibility of the particles during heating can be further improved, and the sintering temperature can be effectively reduced.

[0072] In addition, with respect to copper particles B, when the crystallite size obtained by using the Scherrer formula at half maximum width of the peak originating from the (220) plane of copper in X-ray diffraction measurement is set as the second crystallite size S2, the ratio (S1 / S2) of the first crystallite size S1 to the second crystallite size S2 is also preferably below a specified value.

[0073] Specifically, the S1 / S2 ratio is preferably 1.35 or less, more preferably 0.1 or more and 1.3 or less, and even more preferably 0.1 or more and 1.2 or less.

[0074] From the perspective of the crystal structure of the metal copper that is easy to obtain a face-centered cubic structure, the copper particle B has a copper (111) plane in a specific plane on the particle surface, and a copper (220) plane in the plane intersecting the (111) plane. Moreover, the smaller the S1 / S2 ratio is, the more it indicates that the copper particle has not grown in the (111) plane direction or in the (220) plane direction. Therefore, the above-mentioned range of S1 / S2 is roughly related to the anisotropy of the particle shape such as the copper particle B being a flat shape. The flat shape refers to a shape having a pair of main surfaces opposite to each other and side surfaces intersecting these main surfaces. In the case where the copper particle B is a flat shape, it is inferred that the copper (111) plane exists in the main surface of the copper particle B, and the copper (220) plane exists in the side surface of the copper particle B.

[0075] Therefore, by making the S1 / S2 ratio into the above-mentioned range, when the copper particles B are arranged with each other during sintering, the main surfaces of the copper particles B are easily in contact with each other, or the side surfaces of the particles are easily in contact with each other, and the contact portions of the copper particles B are easily in the same crystal plane. Regarding the particles to which thermal energy is applied, the utilization efficiency of thermal energy is high when the particles are in contact with each other with the same crystal plane compared to the case where the particles are in contact with each other with different crystal planes, and the atoms at the microcrystalline interface become easy to diffuse. As a result, the fusibility of the particles at low temperatures can be improved, and the sintering temperature of the copper powder can be reduced. This is advantageous in that the sinterability can be further improved compared to spherical particles and mechanically manufactured flat copper particles.

[0076] Furthermore, since the copper particles B are in contact with each other in a surface-to-surface manner as described above, the contact area is larger than that of spherical copper particles, etc. For this reason, the conductive film produced from the copper powder of the present invention including the copper particles B has high continuity.

[0077] Such copper particles can be obtained, for example, by the production method described below.

[0078] The second crystallite size S2 of the copper particles B is preferably 10 nm or more and 80 nm or less, more preferably 20 nm or more and 75 nm or less, and further preferably 30 nm or more and 70 nm or less. When the crystallite size S2 is in such a range, the low-temperature sintering property due to the relatively small crystallite size can be improved, and many conductive paths of the shape derived from the copper particles can be formed, and a low-resistance conductive film can be formed after sintering.

[0079] Regarding copper particles B, when the crystallite size obtained by using the Scherrer formula to calculate the half-value width of the peak originating from the (311) plane of copper in X-ray diffraction measurement is set as the third crystallite size S3, the ratio (S1 / S3) of the first crystallite size S1 to the third crystallite size S3 is preferably below a specified value.

[0080] Specifically, the S1 / S3 ratio is preferably 1.35 or less, more preferably 0.20 or more and 1.30 or less, and still more preferably 0.50 or more and 1.25 or less.

[0081] From the perspective of the crystal structure of the metal copper that is easy to obtain a face-centered cubic structure, the copper particle B has a copper (111) surface in a specific surface on the particle surface, and a copper (311) surface in the surface intersecting the (111) surface. Moreover, the smaller the S1 / S3 ratio is, the more it indicates that the copper particle B does not grow in the (111) surface direction or grows in the (311) surface direction. Therefore, the above-mentioned range of S1 / S3 is roughly related to the anisotropy of the particle shape such as the copper particle B being a flat shape. In this case, it is speculated that the copper (111) surface exists in the main surface of the copper particle B, and the copper (311) surface exists in the side of the copper particle.

[0082] Therefore, by making the S1 / S3 ratio into the above range, when the copper particles B are arranged with each other during sintering, the main surfaces of the copper particles B or the side surfaces of the copper particles B are easy to contact with each other, and the contact parts of the copper particles B are easy to become the same crystal plane. As a result, when the copper powder of the present invention is heated, the atomic diffusion of the microcrystalline interface of the copper particles B can be activated, the fusibility of the particles at low temperatures is improved, and the sintering temperature of the copper powder is reduced. This is advantageous in that the sinterability can be further improved compared to spherical particles and mechanically manufactured flat copper particles.

[0083] Such copper particles can be obtained, for example, by the production method described below.

[0084] The third crystallite size S3 of the particle B is preferably 10 nm or more and 80 nm or less, more preferably 20 nm or more and 75 nm or less, and further preferably 30 nm or more and 70 nm or less. When the crystallite size S3 is in such a range, the low-temperature sintering property due to the relatively small crystallite size can be improved, and many conductive paths of shapes derived from the copper particles B can be formed, and a low-resistance conductive film can be formed after sintering.

[0085] The first crystallite size S1, the second crystallite size S2, and the third crystallite size S3 can be calculated from the full width at half maximum of the diffraction peak derived from the (111) plane, (220) plane, or (311) plane of copper obtained by X-ray diffraction measurement, using the Scherrer formula shown below. The conditions for X-ray diffraction measurement are described in detail in the examples described below. PDF number 00-004-0836 is used.

[0086] Scherrer formula: D = Kλ / βcosθ

[0087] D: Crystallite size

[0088] K: Scherrer constant (0.94)

[0089] λ: wavelength of X-rays

[0090] β: Half-value amplitude [rad]

[0091] θ: diffraction angle

[0092] The copper particles B preferably contain copper as the main component. The copper as the main component means that the copper content in the copper particles is 97.0% by mass or more, preferably 97.5% by mass or more, more preferably 98.0% by mass or more, and further preferably 98.5% by mass or more. The copper content can be measured, for example, by ICP emission spectrometry.

[0093] The copper particle B contains other elements other than the copper element in addition to the copper element, or contains the copper element and does not contain other elements other than the copper element except for inevitable impurities. As long as the effect of the present invention is not impaired, the copper particle B is allowed to contain trace amounts of inevitable impurity elements such as oxygen. In any embodiment, the content of other elements other than the copper element in the copper particle is preferably 1.5% by mass or less. The content of these elements can be measured, for example, by ICP emission spectrometry.

[0094] Copper particle B also preferably has a low content of carbon contained in the particle. Specifically, the content of carbon in copper particle B is preferably 5000ppm or less, more preferably 4500ppm or less, and further preferably 4000ppm or less, the less the better, but in reality it is 100ppm or more. By having the content of carbon in such a range, it is relatively possible to suppress the sintering obstacle caused by organic matter present on the surface of copper particles. Such copper particles can be manufactured, for example, by the manufacturing method described later.

[0095] The content of carbon element can be measured by methods such as gas analysis or combustion carbon analysis. When measuring the content of carbon element, first, it is judged whether the copper particle B surface has been covered. The confirmation method can, for example, list the method that the methods such as X-ray photoelectron spectroscopy (XPS), nuclear magnetic resonance (NMR), Raman spectroscopy, infrared spectroscopy, liquid chromatography, time-of-flight secondary ion mass spectrometry (TOF-SIMS) are carried out alone or in combination. If it is judged by the method that the particle surface has been covered, then the above-mentioned method is combined alone or in multiple ways, and the type and amount of the element contained in the covering layer formed by covering are qualitatively analyzed and quantitatively analyzed. In addition, by thermogravimetric determination (TG), by the mass change produced before and after the firing temperature and the measurement of the carbon amount after being heated to the temperature, the physical property of organic matter can be evaluated.

[0096] When it is determined that the particle surface is not coated, the copper particle B to be measured is directly subjected to measurement, and the obtained quantitative value is taken as the carbon element content contained in the copper particle B.

[0097] The copper particle B also preferably has a phosphorus content contained in the particle within a specified range. Specifically, the phosphorus content in the copper particle is preferably 300 ppm or more, more preferably 300 ppm or more and 1500 ppm or less, and further preferably 300 ppm or more and 1000 ppm or more. By setting the phosphorus content to such a range, the electrical conductivity of copper can be fully maintained, and a melting point drop is produced, so that the sintering temperature is further reduced. Such copper particles can be manufactured, for example, by the manufacturing method described later. The presence or absence of phosphorus in the copper particle B and its content can be measured, for example, by ICP emission spectrometry.

[0098] As described above, the less carbon content of the copper particles B is, the less likely it is to cause sintering obstacles, and the copper powder can be sintered at a low temperature. In particular, if the carbon content is within the above range, it is relatively possible to suppress sintering obstacles caused by organic matter present on the surface of the copper particles B, so organic matter can be intentionally applied to the surface of the copper particles B.

[0099] As the organic matter applied to the surface of copper particle B, for example, copper salts of various fatty acids or aliphatic organic acids and aliphatic amines can be listed. By applying such an organic matter to the surface of copper particle B, the coagulation between copper particles can be suppressed. In particular, it is preferred to use a saturated or unsaturated fatty acid or aliphatic amine having a carbon number of more than 6 and less than 18, especially a carbon number of more than 10 and less than 18 from the aspect of the improvement of the low-temperature sintering property of copper powder. As the specific example of such aliphatic acid or aliphatic amine, benzoic acid, valeric acid, caproic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, palmitic acid, oleic acid, stearic acid, amylamine, hexylamine, octylamine, decylamine, laurylamine, oleylamine, stearylamine etc. can be listed. These fatty acids or aliphatic amines can be used alone, or two or more can be used in combination.

[0100] As long as the copper particle B can exert the effect of the present invention, its shape is not particularly limited, but in the case of manufacturing by the method described later, it is preferably a flat shape. Such particles have a pair of substantially flat main surfaces relative to each other and a side surface intersecting with the two main surfaces, and are plate-like particles with a maximum diameter length of the main surface greater than the thickness. In this case, when looking down at the main surface in the copper particle B, its shape also preferably has a profile defined by a combination of straight lines or a combination of straight lines and curves.

[0101] The conductive film produced by the copper paste containing the copper powder of the present invention has high compactness and continuity. From the viewpoint of further improving the compactness and continuity of the conductive film, the content ratio of the copper particles A relative to the total of the copper particles A and the copper particles B is preferably 60% by mass or more and 99% by mass or less, more preferably 65% ​​by mass or more and 88% by mass or less, and further preferably 70% by mass or more and 85% by mass or less.

[0102] From the same viewpoint, the content ratio of copper particles B relative to the total of copper particles A and copper particles B is preferably 1 mass % or more and 40 mass % or less, more preferably 12 mass % or more and 35 mass % or less, and further preferably 15 mass % or more and 30 mass % or less.

[0103] Next, the preferred method for producing the copper powder of the present invention is described. The copper powder of the present invention is preferably produced by mixing copper particles A and copper particles B in the preferred ratio described above. The preferred method for producing copper particles A and copper particles B, and the method for mixing copper particles A and copper particles B are described in detail below.

[0104] <Method for producing copper particles A>

[0105] First, a description is given of a preferred method for producing the copper particles A. In this production method, core particles containing copper are brought into contact with a solution containing a copper salt of an aliphatic organic acid to form a covering layer that covers the surface of the core particles.

[0106] First, before surface treatment with a copper salt of an aliphatic organic acid, core particles containing copper are prepared. As a method for manufacturing copper core particles, for example, it can be manufactured by a wet-based method described in Japanese Patent Gazette No. 2015-168878. That is, a reaction solution containing a monovalent or divalent copper source such as copper chloride, copper acetate, copper hydroxide, copper sulfate, copper oxide or cuprous oxide in a liquid medium containing water and a monohydric alcohol preferably having a carbon number of 1 or more and 5 or less is prepared. The reaction solution and hydrazine are preferably mixed in a ratio of 0.5 moles or more and 50 moles or less relative to 1 mole of copper, and the copper source is reduced to obtain core particles containing copper. The core particles obtained by this method do not have a surface treatment agent such as a copper salt of an aliphatic organic acid applied to their surface, and the particle size is small.

[0107] The core particles obtained in the above-mentioned process are preferably subjected to washing treatment. As washing methods, for example, decantation method, rotary filter method, etc. can be cited. In the case where the core particles are washed by the rotary filter method, for example, an aqueous slurry obtained by dispersing the core particles in a solvent such as water is prepared, and the slurry is washed until the conductivity is preferably less than 2.0 mS. The washing conditions at this time, for example, when using water as a washing solvent, can be set to a washing temperature of more than 15°C and less than 30°C, and a washing time of more than 10 minutes and less than 60 minutes. By setting the conductivity of the slurry to the above-mentioned range, the surface treatment described later can be efficiently performed in a state where the core particles of the washing object are not condensed but uniformly dispersed. From the viewpoint of both improving the washing efficiency and improving the dispersibility of the particles, the content ratio of the core particles containing copper in the slurry is preferably more than 5% by mass and less than 50% by mass.

[0108] In addition, instead of the above method, as another method for manufacturing core particles containing copper, for example, the direct current thermal plasma (DC plasma) method described in the International Publication No. 2015 / 122251 pamphlet can also be used. In detail, the mother powder of copper can be supplied to the direct current thermal plasma method as one of the PVD methods, and the core particles are generated from the mother powder. The core particles obtained by this method also do not have a surface treatment agent such as a copper salt of an aliphatic organic acid applied to its surface, and the particle size is small. As needed, the obtained core particles can also be crushed or graded to separate or remove coarse particles or fine particles.

[0109] Next, the core particles obtained by the above method are surface treated with a surface treatment agent to form a covering layer covering the surface of the core particles. As a surface treatment method, for example, a method of contacting the core particles with a solution obtained by dissolving a copper salt of an aliphatic organic acid in a solvent can be adopted. The form of the core particles contacted with the copper salt of an aliphatic organic acid in this process can be an aqueous slurry obtained by dispersing the core particles in a solvent such as water, or it can be a core particle in a dry state that is not dispersed in a solvent, etc. In addition, as the contact order in this process, one of the core particles and the copper salt solution of an aliphatic organic acid can be added to the other, or the core particles and the solution of the copper salt of an aliphatic organic acid can be contacted at the same time.

[0110] From the viewpoint of uniformly performing the surface treatment of the core particles with the copper salt of an aliphatic organic acid, it is preferable to adopt a method of adding a solution of the copper salt of an aliphatic organic acid to a slurry in which the core particles are dispersed.

[0111] The following description is taken as an example of a method for surface treatment by adding core particles to a copper salt solution of an aliphatic organic acid. First, the solvent used in the copper salt solution of an aliphatic organic acid is heated to a temperature below the boiling point of the solvent used (for example, above 25°C and below 80°C), and in this state, the copper salt of an aliphatic organic acid is added to the solvent to prepare a copper salt solution of an aliphatic organic acid. Next, while maintaining the temperature of the copper salt solution above the melting point of the copper salt of an aliphatic organic acid, the core particles or the slurry containing the core particles in a dry state are added to the copper salt solution of an aliphatic organic acid, and then stirred for 1 hour to perform surface treatment on the surface of the core particles. The copper particles A obtained by this method become copper particles having a coating layer formed by the copper salt of an aliphatic organic acid on the surface of the core particles containing copper. In the case of using a core particle-containing slurry for surface treatment, it is preferred that the slurry is heated to a temperature above the melting point of the copper salt of an aliphatic organic acid from the viewpoint of uniformly forming a coating layer on the surface of the core particles.

[0112] In the surface treatment using a solution of a copper salt of an aliphatic organic acid, the content of the copper salt of an aliphatic organic acid in the reaction solution containing the core particles is preferably set to 0.1 mass parts or more and 3.0 mass parts or less, more preferably 0.2 mass parts or more and 2.0 mass parts or less relative to 100 mass parts of core particles not subjected to surface treatment. By performing surface treatment in such an amount, copper particles A surface-treated at the above-mentioned carbon atom ratio can be obtained.

[0113] The solvent for dissolving the copper salt of an aliphatic organic acid may include organic solvents such as monohydric alcohols, polyhydric alcohols, esters of polyhydric alcohols, ketones, and ethers having a carbon number of 1 to 5. Among them, monohydric alcohols having a carbon number of 1 to 5 are preferably used, and methanol aqueous solution, ethanol, 1-propanol, or isopropyl alcohol are more preferably used from the viewpoint of compatibility with water, economy, operability, and ease of removal.

[0114] After the copper particles A obtained through the above steps are washed or solid-liquid separated as needed, the copper particles A can be dispersed in a solvent such as water or an organic solvent to obtain a slurry and mixed with the copper particles B. Alternatively, the copper particles A can be dried and mixed with the copper particles B in the form of a collection of copper particles, i.e., a dry powder. In either case, by including the copper particles A in the copper powder of the present invention, it is possible to obtain an excellent copper powder that can suppress oxidation of copper as a constituent metal, suppress aggregation of particles, and has a low sintering temperature.

[0115] <Method for producing copper particles B>

[0116] Next, a preferred method for producing copper particles B is described. This production method includes two reduction steps: a first reduction step of reducing copper ions to produce cuprous oxide, and a second reduction step of reducing cuprous oxide in the presence of diphosphoric acid or higher polyphosphoric acid or salts thereof (hereinafter also referred to as polyphosphoric acids) to produce copper particles.

[0117] The polyphosphoric acid is present in the reaction system at a certain stage when the second reduction step is performed or before the second reduction step is performed. That is, the polyphosphoric acid may be present in the reaction system before the first reduction step or when the first reduction step is performed, and the second reduction step is performed in this state. Alternatively, the polyphosphoric acid may be present in the reaction system after the first reduction step is completed, when the second reduction step is performed or before the second reduction step is performed, without causing the polyphosphoric acid to be present in the reaction system in the first reduction step.

[0118] From the viewpoint of uniform control of the reduction reaction, improved productivity of the copper particles obtained thereby, and reduced manufacturing costs, it is preferred that any reduction step of the present production method is carried out under wet conditions of reduction in an aqueous liquid, and it is also preferred that any reduction step is carried out in the same reaction system. Below, the production method under wet conditions and in the same reaction system will be described as an example.

[0119] First, a reaction solution containing a copper source and a reducing compound is prepared and a first reduction step is performed to reduce copper ions and generate cuprous oxide in the solution. The reaction solution can be prepared by adding each raw material to a solvent at the same time to prepare the reaction solution, or each raw material can be added to the solvent in an arbitrary order.

[0120] From the viewpoint of easy control of the reduction reaction of copper ions and improvement of operability during manufacture, it is preferred that: after the copper source and the solvent are pre-mixed to form a copper-containing solution, a solid reducing compound or a reducing compound solution pre-dissolved in a solvent is added to the copper-containing solution. The reducing compound can be added all at once or successively.

[0121] In the first reduction step, as described above, the reaction solution may contain polyphosphoric acids or may not contain them. When the reaction solution contains polyphosphoric acids, it is preferred to sequentially add the copper source, polyphosphoric acids, and the reducing compound from the perspective of effectively reducing the copper ions using the reducing compound and controlling the crystal growth.

[0122] As the solvent in the reaction solution, water or a lower alcohol such as methanol, ethanol, or propanol can be used, and these can be used alone or in combination of two or more.

[0123] As the copper source used in the first reduction step, compounds that generate copper ions in the reaction solution can be listed, and preferably water-soluble copper compounds can be listed. As specific examples of such copper sources, various copper compounds such as copper organic acid salts such as copper formate, copper acetate, and copper propionate, and copper inorganic acid salts such as copper nitrate and copper sulfate can be listed. These copper compounds can be anhydrous or hydrated. These copper compounds can be used alone or in combination.

[0124] The content of the copper source in the reaction system in the first reduction step is expressed as a molar concentration of the copper element, preferably 0.01 mol / L or more and 2.0 mol / L or less, more preferably 0.1 mol / L or more and 1.5 mol / L or less. By being within such a range, copper particles having a small particle size and a small crystallite size in a specific crystal plane can be produced with high productivity.

[0125] As the reducing compound, water-soluble compounds can be preferably listed. As specific examples of the reducing compound, hydrazine compounds such as hydrazine, hydrazine hydrochloride, hydrazine sulfate and hydrazine hydrate, boron compounds such as sodium borohydride and dimethylamine borane and their salts, sulfur oxyacid salts such as sodium sulfite, sodium bisulfite and sodium thiosulfate, nitrogen oxyacid salts such as sodium nitrite and sodium hyponitrite, phosphorous acid, sodium phosphite, hypophosphorous acid and sodium hypophosphite and their salts can be listed. These reducing compounds can be anhydrous or hydrated. These reducing compounds can be used alone or in combination of two or more.

[0126] From the viewpoints of easily controlling the reduction product in the first reduction step to become cuprous oxide, easily controlling the grain growth of copper in the subsequent reduction step and easily obtaining particles having a predetermined crystallite size, and reducing the unintentional mixing of impurities such as carbon elements after reduction, it is preferred to use a hydrazine compound as the reducing compound in the reducing solution, and it is further preferred to use an anhydrate or a hydrate of hydrazine.

[0127] The content of the reducing compound in the reaction solution in the first reduction step is preferably set to 0.1 mol or more and 2 mol or less, and more preferably 0.1 mol or more and 1 mol or less, relative to 1 mol of the copper element. By controlling the concentration of the reducing compound to such a range, the reduction reaction of copper ions and the progress of grain growth can be appropriately controlled, and copper particles with a small grain size and a small crystallite size in a specific crystal plane can be obtained with high productivity.

[0128] The reaction liquid in the first reduction step is preferably set to an acidic condition in which the pH at 25° C. is 3 or more and 5 or less in terms of the following aspects: when a reducing compound, particularly a hydrazine compound, is used, the degree of reducing property can be appropriately controlled to such an extent that reduction to cuprous oxide is performed and reduction to metallic copper is not performed, and the copper crystal growth performed in the second reduction step can be easily anisotropic. In the first reduction step, adding the reducing compound after adjusting the pH is preferred in terms of being able to appropriately control the degree of reduction of copper ions.

[0129] As long as the effect of the present invention can be brought into play, the pH can be adjusted by using various acids or alkaline substances or by making the reaction solution have polyphosphoric acids. In particular, in the adjustment of pH, by using polyphosphoric acids, even if other substances are not added to the reaction system, subsequent reactions can be effectively carried out, so it is advantageous to prevent the mixing of unintended impurities and to effectively obtain the target copper particles.

[0130] The reduction reaction in the first reduction step can be carried out in a non-heated state or in a heated state. In either case, the temperature of the reaction solution is preferably set to be above 10°C and below 60°C, more preferably above 20°C and below 50°C. The reaction time in the first reduction step is preferably set to be above 0.1 hour and below 2 hours, more preferably above 0.2 hour and below 1 hour, with the above-mentioned temperature range as a condition. In addition, from the viewpoint of the uniformity of the reduction reaction, it is also preferred to continue stirring the reaction solution from the start of the reaction to the end of the reaction.

[0131] Next, a second reduction step is performed to reduce the cuprous oxide obtained in the first reduction step to generate metal copper particles. The second reduction step is also preferably performed under wet conditions like the first reduction step, and both reduction steps are more preferably performed in the same reaction system.

[0132] As described above, it is preferred that polyphosphoric acid is present in the reaction system during the second reduction step or at any stage before the second reduction step. Examples of polyphosphoric acid used in the present production method include diphosphoric acid (H4P2O7), triphosphoric acid (tripolyphosphoric acid, H5P3O7), and polyphosphoric acid (H5P3O7). 10 ), tetrapolyphosphoric acid (H6P4O 13 ) and the like, and polyphosphoric acids and their salts having preferably 2 or more and 8 or less, more preferably 2 or more and 5 or less phosphoric acid monomer units in the structure. As polyphosphates, alkali metal salts, alkaline earth metal salts, other metal salts, ammonium salts, etc. can be listed. They can be used alone or in combination.

[0133] The content of polyphosphoric acid in the second reduction process is preferably set to 0.1 millimole or more, more preferably 0.1 millimole or more and 1 mole or less relative to 1 mole of copper element. By setting the concentration of polyphosphoric acid to such a range, the crystal growth of copper caused by the reduction reaction of cuprous oxide can be carried out in an anisotropic manner, and copper particles with small particle size and small crystallite size in a specific crystal plane can be obtained with high productivity. It should be noted that, when polyphosphoric acid is contained at the moment of the first reduction process, since polyphosphoric acid is not consumed in the reaction in the first reduction process, the concentration of polyphosphoric acid does not substantially change before and after the first reduction process, so by adding polyphosphoric acid to the reaction system in the above-mentioned concentration range in the first reduction process, the amount of polyphosphoric acid suitable for the reduction and particle growth of metallic copper in the second reduction process can be fully achieved.

[0134] In the second reduction step, the above-mentioned reducing compound can be added to perform reduction to metallic copper. The content of the reducing compound in the reaction solution in the second reduction step is preferably set to 1 mol or more and 8 mol or less, more preferably 2 mol or more and 6 mol or less relative to 1 mol of the copper element. In the case where the second reduction step is performed by the same reaction system as the first reduction step, from the viewpoint of controlling both the improvement of reducibility and the reduction of impurities, it is preferred to further add the reducing compound to the solution in a manner to achieve the above-mentioned content. In addition, it is also preferred that the same type of reducing compound is used in each reduction step.

[0135] By controlling the concentration of the reducing compound to fall within such a range, the reduction reaction to metallic copper can be sufficiently advanced, and copper particles having a small particle size and a small crystallite size in a specific crystal plane can be obtained with high productivity.

[0136] The reducing compound in the second reduction step may be added all at once or sequentially. From the viewpoint of efficiently obtaining copper particles satisfying the above-mentioned crystallite size ratio or particle size, sequential addition is preferred.

[0137] The reaction solution in the second reduction step is set to a non-acidic condition (neutral or alkaline condition) with a pH of 7.0 or more at 25°C. It is preferred in the following aspects: when using a reducing compound, especially a hydrazine compound, the copper ions and cuprous oxide remaining in the reaction solution can be effectively reduced to metallic copper, and the crystal growth of copper is easily anisotropic. It is preferred that the pH is adjusted before adding the reducing compound in the second reduction step in order to appropriately control the degree of reduction of the copper ions. Various acids or alkaline substances can be used to adjust the pH.

[0138] When the second reduction step is performed in the same reaction system as the first reduction step, the reaction solution after the first reduction step becomes acidic, so it is preferred to adjust the pH of the reaction solution by adding an alkaline substance such as sodium hydroxide or potassium hydroxide. In the second reduction step, adding a reducing compound after adjusting the pH is preferred in that copper ions and cuprous oxide can be effectively reduced to metallic copper.

[0139] From the viewpoint of efficiently reducing the copper ions and cuprous oxide in the reaction solution and obtaining copper particles with a predetermined crystallite size with high productivity, the reaction solution is preferably heated in the second reduction step. The heating conditions of the reaction solution are preferably maintained at 10°C or more and 60°C or less, particularly 20°C or more and 50°C or less from the start time of the second reduction step, that is, the time of adding the reducing compound to the end time of the reaction. The reaction time is preferably set to 30 minutes or more and 720 minutes or less under the above-mentioned temperature conditions. In addition, from the viewpoint of uniformly generating the reduction reaction and obtaining copper particles with less uneven particle size, it is also preferred to continue stirring the reaction solution from the start time of the reaction to the end time of the reaction.

[0140] The present inventors speculate as follows why copper particles with a low sintering temperature can be obtained by performing a two-step reduction step in which copper ions are reduced to metallic copper via cuprous oxide and by the presence of polyphosphoric acid in the second reduction step in the present production method.

[0141] First, in the first reduction step, copper ions are reduced by the reducing compound in the reaction solution, and very small particles of cuprous oxide are generated in the reaction solution. Then, in the second reduction step, the monovalent copper ions dissolved from the cuprous oxide particles are reduced to form the core of metallic copper. Since the core is very unstable, the cores are repeatedly combined with each other or redissolved in the reaction solution, and finally the particles gradually grow. If polyphosphoric acid is present when the particles grow, the polyphosphoric acid is adsorbed on a specific crystal face of copper, and the growth in the direction of the crystal face is suppressed. On the other hand, the growth of the crystal face without the adsorption of polyphosphoric acid is not suppressed, and the growth in the direction of the crystal face progresses.

[0142] Based on the fact that metallic copper easily adopts a face-centered cubic crystal structure and the results of X-ray diffraction measurement of the obtained copper particles, it is estimated that the crystal plane adsorbed with polyphosphoric acid is the copper (111) plane in the particles, and the crystal plane not adsorbed with polyphosphoric acid is the copper (220) plane located in the perpendicular direction to the copper (111) plane. It is therefore believed that the growth of the copper (111) plane is suppressed and the growth of the copper (220) plane progresses, resulting in anisotropic growth, and thus flat copper particles with a low sintering temperature are obtained.

[0143] In addition, as the preferred manufacturing method of copper particle B, particularly by carrying out reduction reaction with acidic conditions in the 1st reduction step, it is possible to control the reducing power of the degree that copper ions can be reduced to cuprous oxide and cannot be reduced to metallic copper. In addition, the control of the subsequent metallic copper generation reaction also becomes easy. Afterwards, by being set to non-acidic conditions, the dissolution rate of cuprous oxide can be reduced, and the monovalent copper ion supply is controlled. By carrying out the 2nd reduction under this environment, the reduction reaction rate to metallic copper can be adjusted to slow conditions, so it is particularly advantageous in terms of being able to control the nuclear growth rate.

[0144] The copper particles B obtained through the above steps become copper particles that satisfy the above-mentioned preferred crystallite size and its ratio, preferred particle size, preferred content of various elements such as carbon element, even if they do not contain organic components that control crystal growth such as organic amines or amino alcohols, reducing sugars, etc., and also become copper particles with a flat shape.

[0145] In addition, the copper particles B obtained in this way become copper particles in which the crystal planes of the crystals existing on the main surface and growing in the direction perpendicular to the main surface and the crystal planes of the crystals existing on the side and growing in the direction along the main surface have specific orientation directions, respectively, and each crystal plane is uniformly formed in one direction. Therefore, when copper powder containing copper particles B is used and sintering is performed in a state where the main surfaces of the copper particles B are in contact with each other, or the side surfaces of the copper particles B are in contact with each other, since the same crystal planes arranged evenly are in contact with each other, sintering at a low temperature is possible without excessively requiring energy required for fusion.

[0146] After the copper particles B obtained by the above process are washed or solid-liquid separated as needed, the copper particles B can be mixed with the copper particles A in the form of a slurry obtained by being dispersed in a solvent such as water or an organic solvent, or the particles can be dried and mixed with the copper particles A in the form of an aggregate of copper particles B, i.e., a dry powder. In either case, copper particles B become excellent copper particles with low sintering temperatures. Copper particles B can also be further surface-coated using inorganic substances such as organic substances such as fatty acids or their salts, silicon-based compounds, etc., for the purpose of improving the dispersibility of particles as needed. It should be noted that, as long as the effect of the present invention can be exerted, the copper particles B obtained are allowed to be inevitably trace-oxidized on their surface, etc., including other elements other than copper element.

[0147] <Method of Mixing Copper Particles A and Copper Particles B>

[0148] Copper particles A and copper particles B can be mixed in a dry or wet manner, but from the perspective of the simplicity of mixing, it is preferably mixed in a dry manner. Dry mixing can be performed using a known dry mixing device. Wet mixing can be specifically mixed in an organic solvent or an aqueous solvent.

[0149] The copper powder of the present invention may be further dispersed in an organic solvent, resin or the like and used in the form of a conductive composition such as a conductive ink or a copper paste.

[0150] When the copper powder of the present invention is set as the form of a conductive composition, the conductive composition comprises at least copper powder and an organic solvent. As an organic solvent, the same organic solvent used so far in the technical field of conductive compositions containing metal powders can be used without particular limitation. As such an organic solvent, for example, monohydric alcohols, polyols, polyol alkyl ethers, polyol aryl ethers, polyethers, esters, nitrogen-containing heterocyclic compounds, amides, amines, and saturated hydrocarbons can be cited. These organic solvents can be used alone or in combination of two or more. Among them, from the viewpoint of having a high reducing effect and preventing the unintentional oxidation of copper particles during sintering, polyethers such as polyethylene glycol and polypropylene glycol are preferably used. From the same viewpoint, when polyethylene glycol is used as an organic solvent, its number average molecular weight is preferably 120 or more and 400 or less, and more preferably 180 or more and 400 or less.

[0151] In the conductive composition containing the copper powder of the present invention, at least one of a dispersant, an organic vehicle and a glass powder may be further added as needed. As the dispersant, a dispersant such as a nonionic surfactant that does not contain sodium, calcium, phosphorus, sulfur and chlorine, etc. may be cited. As the organic vehicle, for example, a mixture of a solvent including a resin component such as an acrylic resin, an epoxy resin, ethyl cellulose, and carboxyethyl cellulose and a terpene solvent such as terpineol and dihydroterpineol, an ether solvent such as ethyl carbitol and butyl carbitol may be cited. As the glass frit, for example, borosilicate glass, barium borosilicate glass, zinc borosilicate glass, etc. may be cited.

[0152] The conductive composition containing the copper powder of the present invention can be applied to a substrate to form a coating film and the coating film is fired to form a conductive film containing copper. The conductive film can be suitably used, for example, to ensure the electrical conduction of the external electrodes of a printed circuit wiring board and a ceramic capacitor. As a substrate, a printed substrate formed of a glass epoxy resin or the like, a flexible printed substrate formed of a polyimide or the like can be cited depending on the type of electronic circuit using the copper particles.

[0153] The amount of copper powder and organic solvent in the conductive composition containing the copper powder of the present invention can be adjusted according to the specific use of the conductive composition or the coating method of the conductive composition, but the content of copper powder in the conductive composition is preferably 5% by mass or more and 95% by mass or less, more preferably 80% by mass or more and 90% by mass or less. As the coating method, for example, an inkjet method, a dispensing method, a microdispensing method, a gravure printing method, a screen printing method, a dip coating method, a spin coating method, a spray coating method, a rod coating method, a roller coating method, etc. can be used.

[0154] The heating temperature when sintering the formed coating film can be set to be above the sintering start temperature of the copper powder, for example, above 150°C and below 220°C. The atmosphere during heating can be carried out, for example, in an oxidizing atmosphere or in a non-oxidizing atmosphere. As an oxidizing atmosphere, for example, an oxygen-containing atmosphere can be listed. As a non-oxidizing atmosphere, for example, a reducing atmosphere such as hydrogen, carbon monoxide, a weakly reducing atmosphere such as a hydrogen-nitrogen mixed atmosphere, an inactive atmosphere such as argon, neon, helium and nitrogen can be listed. When using any atmosphere, the heating time is set to preferably be more than 1 minute and less than 3 hours, and more preferably be more than 3 minutes and less than 2 hours, with heating being carried out within the above-mentioned temperature range as a condition.

[0155] Since the conductive film thus obtained is obtained by sintering the copper powder of the present invention, it can be fully sintered even when sintering is performed under relatively low temperature conditions. In addition, during sintering, the copper particles constituting the copper powder melt even at low temperatures, so the contact area between the copper particles or between the copper particles and the surface of the substrate can be increased, and as a result, a sintered structure with high adhesion to the object to be joined and a dense structure can be efficiently formed. Furthermore, the conductive film obtained becomes a conductive film with high continuity, density and conductive reliability.

[0156] The present invention has been described above based on preferred embodiments thereof, but the present invention is not limited to the above embodiments. For example, the copper powder of the present invention may contain copper particles other than the copper particles A and the copper particles B within a range that exhibits a desired effect.

[0157] The above-mentioned embodiments of the present invention include the following technical ideas.

[0158] [1] A copper powder comprising the following copper particles A and copper particles B, wherein:

[0159] The content ratio of copper particles A relative to the total of copper particles A and copper particles B is 60 mass % or more and 99 mass % or less, and the content ratio of copper particles B is 1 mass % or more and 40 mass % or less.

[0160] 〔Copper particles A〕

[0161] The copper particle includes a core particle containing copper and a covering layer covering a surface of the core particle.

[0162] The above-mentioned coating layer is formed of a copper salt of an aliphatic organic acid.

[0163] The primary particle size is 0.1 μm or more and 0.6 μm or less.

[0164] 〔Copper particles B〕

[0165] For the copper particles, a ratio (S1 / B) of a first crystallite size S1 obtained by the Scherrer equation from the half-value width of a peak originating from the (111) plane of copper in X-ray diffraction measurement to a BET diameter B calculated from a BET specific surface area is 0.23 or less,

[0166] The ratio (S1 / S2) of the first crystallite size S1 to the second crystallite size S2 obtained by the Scherrer equation from the half-value width of the peak derived from the (220) plane of copper in X-ray diffraction measurement is 1.35 or less,

[0167] The primary particle size is 0.1 μm or more and 2.0 μm or less.

[0168] [2] The copper powder according to [1], wherein the ratio (S1 / S3) of the first crystallite size S1 of the copper particles B to the third crystallite size S3 calculated by the Scherrer equation from the half-value width of the peak originating from the (311) plane of copper in X-ray diffraction measurement is less than 1.35.

[0169] [3] The copper powder according to [1] or [2], wherein the copper particles B contain carbon element, and the content of the carbon element is 5000 ppm or less.

[0170] [4] The copper powder according to any one of [1] to [3], wherein the copper particles B contain phosphorus, and the content of the phosphorus is 300 ppm or more.

[0171] [5] A copper paste comprising the copper powder according to any one of [1] to [4].

[0172] [6] A method for producing a conductive film, comprising: applying the copper paste described in [5] on a substrate to form a coating film, and firing the coating film.

[0173] Example

[0174] Hereinafter, the present invention will be described in more detail by way of examples. However, the scope of the present invention is not limited to the examples. Unless otherwise specified, "%" means "mass %".

[0175] In the following examples and comparative examples, copper particles A-1, A-2, and B-1 to B-3 were used as copper particles. Among them, spherical copper particles described in Japanese Patent Application Laid-Open No. 2015-168878 were used as copper particles A-2.

[0176] Other copper particles were produced by the following method.

[0177] [Manufacturing of Copper Particles A-1]

[0178] According to the method described in Example 1 of Japanese Patent Publication No. 2015-168878, a slurry obtained by dispersing spherical core particles (copper: 100% by mass) without applying a surface treatment agent in water is manufactured. The slurry is washed at 25° C. for 30 minutes through a rotary filter to obtain a slurry of washed core particles. The conductivity after washing is 1.0 mS, and it has a spherical shape. In addition, the content of the core particles containing copper in the slurry is 1000 g (10% by mass).

[0179] Next, the slurry of the washed core particles was heated to 50°C, and in this state, a solution obtained by dissolving 17g of copper laurate (II) in 4L of isopropyl alcohol was instantaneously added as a surface treatment agent, and stirred at 50°C for 1 hour. After that, solid-liquid separation was performed by filtration to obtain copper particles having a coating layer of a copper salt of an aliphatic organic acid formed on the surface of the core particles as a solid component. The content of the surface treatment agent of the obtained copper particles was 0.7% by mass in terms of carbon atoms.

[0180] Next, the following evaluations were performed on copper particles A-1 and A-2.

[0181] [Measurement of the average image analysis diameter of primary particles]

[0182] The average image analysis diameter of the primary particles of the copper particles was measured by the above-mentioned method. The results are shown in Table 1 below.

[0183] [Calculation of BET diameter A based on BET specific surface area]

[0184] First, the specific surface areas of the copper particles A-1 and A-2 were measured by the above-mentioned measurement method based on the BET one-point method, and the BET diameter A was calculated based on the specific surface areas.

[0185] [Evaluation of temperature at 10% mass loss]

[0186] In the thermogravimetric analysis when heated from 25° C. to 1000° C., the temperature at which the ratio of the mass reduction value to the mass reduction value at 500° C. became 10% was measured under the above-mentioned conditions. The results are shown in Table 1.

[0187] 〔Evaluation of infrared absorption peak〕

[0188] The copper particles A-1 and A-2 were measured by infrared spectroscopy using the above-mentioned method. -1 Above and 1514cm -1 Below, and 1584cm -1 Over 1596cm -1 The copper particles having an infrared absorption peak were evaluated as “present” and the copper particles not having an infrared absorption peak were evaluated as “absent” independently within the following respective ranges. The results are shown in Table 1.

[0189] Table 1

[0190]

[0191] [Manufacturing of copper particles B-1]

[0192] <First reduction step>

[0193] In a stainless steel tank filled with 5.0 liters of warm pure water and 5.0 liters of methanol, 2.5 kg of copper acetate monohydrate as a copper source and 8.0 g of sodium tripolyphosphate as a polyphosphoric acid (molar ratio relative to 1 mol of copper element: 0.002) were added, and the mixture was stirred at a liquid temperature of 25°C for 30 minutes to dissolve the two.

[0194] Next, 235.0 g of hydrazine (molar ratio to 1 mol of copper element: 1.55) was added to the solution, and stirring was continued for 30 minutes at a liquid temperature of 25° C. without heating to generate cuprous oxide particles in the solution. After the generation of cuprous oxide, the reaction solution was stirred for 30 minutes.

[0195] <Second Reduction Step>

[0196] Next, a 25% NaOH aqueous solution was added to the reaction solution in the first reduction step to adjust the pH of the solution to 7.0. Thereafter, the solution temperature was heated to 40°C, and 1900.0 g of hydrazine (molar ratio relative to 1 mol of copper element: 3.0) was quantitatively added to the solution over 10 minutes to perform the second reduction step. Thereafter, the solution was cooled so that the solution temperature reached 30°C, and stirring was continued for 150 minutes to obtain copper particles in which the cuprous oxide particles were reduced to metallic copper.

[0197] The aqueous slurry of the copper particles thus obtained was washed by decantation until the electrical conductivity reached 1.0 mS (washed slurry).

[0198] The slurry of the washed core particles is heated to 50°C. In this state, a solution obtained by dissolving 4g of copper laurate (II) in 1L of isopropyl alcohol is instantaneously added as a surface treatment agent, and stirred at 50°C for 1 hour. Afterwards, solid-liquid separation is performed by filtration to obtain copper particles having a coating layer of copper salt of an aliphatic organic acid formed on the surface of the core particles as a solid component. Afterwards, drying is performed to obtain a copper powder consisting of an aggregate of copper particles. The copper content in the obtained copper particles exceeds 98% by mass and has a flat shape.

[0199] [Manufacturing of copper particles B-2]

[0200] Copper particles B-2 were obtained in the same manner as copper particles B-1 except that the amount of sodium tripolyphosphate added was 24 g (molar ratio to 1 mol of copper element: 0.006). The obtained copper particles had a copper element content of more than 98% by mass and had a flat shape.

[0201] [Manufacturing of copper particles B-3]

[0202] 4 kg of copper sulfate pentahydrate and 120 g of aminoacetic acid were dissolved in water to prepare 8 L of copper salt aqueous solution at a liquid temperature of 70 ° C. Then, while stirring the aqueous solution, 6.6 kg of 25% by mass sodium hydroxide solution was added at a constant speed for about 5 minutes. Next, by stirring at a liquid temperature of 70 ° C for 60 minutes, the liquid color was ripened until it completely turned black to generate copper oxide. After standing for 30 minutes, 1.5 kg of glucose was added and ripened for 1 hour, thereby reducing the copper oxide to cuprous oxide. Furthermore, 1 kg of hydrazine hydrate was quantitatively added for 5 minutes to reduce the cuprous oxide to metallic copper and generate copper powder slurry. The obtained copper powder slurry was filtered, washed thoroughly with pure water, filtered again, and dried. The obtained Cu powder was plastically deformed using the flattening method described in Japanese Patent No. 4227373, so that the roughly spherical copper powder was made into a flat copper powder. At this time, the bead diameter used was not 0.7 mm, but changed to 0.2 mm.

[0203] Next, the following evaluations were performed on copper particles B-1 to B-3.

[0204] [Measurement of the average image analysis diameter of primary particles]

[0205] The average image analysis diameter of primary particles of each of the copper particles B-1 to B-3 was measured by the above-mentioned method.

[0206] [Calculation of BET diameter B based on BET specific surface area]

[0207] The BET diameters B of copper particles B-1 to B-3 were measured in the same manner as the BET diameter A of copper particles A. The results are shown in Table 2 below.

[0208] 〔Determination of carbon and phosphorus element contents〕

[0209] Regarding the carbon element content in the copper particles of copper particles B-1 to B-3, using a carbon / sulfur analyzer (CS844 manufactured by LECO Japan Co., Ltd.), 0.50 g of any one of copper particles B-1 to B-3 was added to a magnetic crucible, the carrier gas was set to oxygen (purity: 99.5%), and the analysis time was set to 40 seconds for measurement. The measurement results are shown in Table 2 below.

[0210] Regarding the phosphorus element content in the copper particles, the solution obtained by dissolving 1.00 g of any one of copper particles B-1 to B-3 in 50 mL of 15% nitric acid aqueous solution was introduced into an ICP emission spectrometer (PS3520VDDII manufactured by Hitachi High-Tech Science Co., Ltd.) for measurement. The measurement results are shown in Table 2 below.

[0211] 〔Determination of crystallite size〕

[0212] For copper particles B-1 to B-3, the measurement was carried out by the following method. First, using the washing slurry of copper particles B-1 to B-3, a 20 mass% aqueous slurry was prepared. Then, an isopropyl alcohol solution obtained by dissolving 12 g of copper laurate as a surface covering treatment agent was added to the slurry heated to 50 °C at one time, and stirred for 1 hour. Then, the solid component obtained by solid-liquid separation by filtration was vacuum dried to obtain copper particles subjected to surface covering treatment. The copper powder was classified using a sieve with a mesh size of 75 μm, and the fraction passing through the sieve was used as a sample. This sample was filled into a sample holder, and using an X-ray diffractometer (Ultima IV manufactured by Rigaku Corporation), the measurement was carried out under the following conditions.

[0213] After that, taking the main peak at the position corresponding to the (220) plane, (111) plane or (311) plane of copper in the diffraction peak as the object, based on the full width at half maximum of this peak, using the above-mentioned Scherrer formula, the crystallite sizes S1 to S3, and the S1 / S2 and S1 / S3 ratios were calculated. In addition, the S1 / B ratio was calculated from the obtained crystallite sizes. The results are shown in Table 2 below.

[0214] <X-ray diffraction measurement conditions>

[0215] · Tube target: CuKα ray

[0216] · Tube voltage: 40 kV

[0217] · Tube current: 50 mA

[0218] · Measured diffraction angle: 2θ = 20 - 100°

[0219] · Measurement step size: 0.01°

[0220] · Collection time: 3 sec / step size

[0221] · Receiving slit width: 0.3 mm

[0222] · Divergent longitudinal limiting slit width: 10 mm

[0223] · Detector: High-speed one-dimensional X-ray detector D / teX Ultra250

[0224] <Preparation method of sample for X-ray diffraction>

[0225] Spread the copper powder to be measured evenly in the measurement holder, and use a glass plate to smooth it so that the thickness of the copper powder becomes 0.5 mm and is smooth.

[0226] Use the X-ray diffraction pattern obtained under the above measurement conditions, and use analysis software to analyze it according to the following conditions. For the analysis, the peak width correction was performed using the LaB6 value. The crystallite size was calculated using the full width at half maximum of the peak and the Scherrer constant (0.94).

[0227] <Measurement data analysis conditions>

[0228] · Analysis software: PDXL2 manufactured by Rigaku

[0229] · Smoothing process: Gaussian function, smoothing parameter = 10

[0230] · Background removal: Fitting method

[0231] · Kα2 removal: Intensity ratio 0.497

[0232] · Peak search: Second derivative method

[0233] · Curve fitting: FP method

[0234] · Crystallite size distribution type: Lorentz model

[0235] · Scherrer constant: 0.9400

[0236] It should be noted that the peaks of the X-ray diffraction pattern used in the analysis are as follows. The Miller indices shown below have the same meaning as the crystal planes of copper mentioned above.

[0237] A peak indexed by the Miller index (220) in the vicinity of 2θ=71° to 76°.

[0238] A peak indexed by the Miller index (111) in the vicinity of 2θ=40° to 45°.

[0239] A peak indexed by the Miller index (311) in the vicinity of 2θ=87.5° to 92.5°.

[0240] Table 2

[0241]

[0242] [Examples 1 to 7 and 9 and Comparative Examples 1 to 7]

[0243] Copper particles A-1, A-2, and B-1 to B-3 were mixed in the ratio shown in Table 3 below to obtain copper powders of each embodiment and each comparative example. Specifically, each copper particle was added to a 100 mL container in the ratio shown in Table 3, and then mixed using a small ball mill (AV-1 manufactured by Asahi Rika Seikakusho) to obtain copper powders of each embodiment and each comparative example. Mixing was performed at 100 rpm for 1 hour.

[0244] The copper powder obtained as described above and polyethylene glycol having a number average molecular weight of 200 were mixed using a three-roll kneader to obtain a copper paste containing 85% by mass of the copper powder.

[0245] In addition, the content of each copper particle component with respect to 100 parts by mass of the total copper particles is shown in Table 3. Moreover, "solid content concentration" shows the ratio of the mass of copper powder to the mass of the whole copper paste.

[0246] [Evaluation of paste printability]

[0247] The paste printability of each Example and each Comparative Example was evaluated based on the following evaluation criteria.

[0248] <Evaluation Criteria for Paste Printability>

[0249] Yes: Can be applied to a glass plate masked with a size of 2 cm in length and 1 cm in width.

[0250] No: It is not possible to form a continuous coating film under the above conditions.

[0251] 〔Manufacturing of conductive films〕

[0252] The copper paste of each example and each comparative example was applied on a glass substrate, and the substrate was fired at 190° C. for 10 minutes in a nitrogen atmosphere to form a conductive film on the glass substrate.

[0253] The obtained conductive film had a length of 2 cm, a width of 1 cm, and a thickness of 30 μm, and was evaluated as follows.

[0254] [Evaluation of film strength]

[0255] The film strength of each conductive film was evaluated based on the following evaluation criteria.

[0256] <Evaluation Criteria for Film Strength>

[0257] High: Scrape the surface of the conductive film without any powder on your hands.

[0258] Low: Scratching the surface of the conductive film will cause powder on your hands.

[0259] [Measurement of resistivity of conductive film]

[0260] The resistivity of each conductive film was measured using a resistivity meter (Mitsubishi Chemical Analytech Co., Ltd., Loresta-GP MCP-T610). The conductive film to be measured was measured three times, and the arithmetic mean value was taken as the resistivity (μΩ·cm). The lower the resistivity, the lower the resistance of the conductive film, preferably 50 μΩ·cm or less. The results are shown in Table 3 below.

[0261] 〔Evaluation of thickness of conductive film〕

[0262] The thickness of the fired film of the Cu paste was measured using a digital length measuring machine (MFC-101 manufactured by Nikon Corporation) to measure the thickness of the conductive film and the glass substrate and the thickness of the glass substrate alone, and the difference between these thicknesses was determined as the thickness of the conductive film.

[0263] [Measurement of surface roughness Ra of conductive film]

[0264] The surface roughness (average roughness Ra) of each conductive film was measured at three locations using a surface roughness / contour measuring instrument (SURFCOM 130A manufactured by Tokyo Seimitsu Co., Ltd.), and the average value of the obtained values ​​was calculated.

[0265] From the viewpoint of electrical resistance, the surface roughness Ra is preferably 2.0 or less. In addition, a small surface roughness Ra of the conductive film means that the conductive film has high density.

[0266] [Measurement of bonding strength]

[0267] For a 5 mm square copper chip polished on one side with a #800 polishing sheet, a copper paste was screen-printed in a shape of 2 mm × 2 mm × 30 μm on the polished side, and a 3 mm square copper chip polished on one side with a #800 polishing sheet was placed so that the polished surface became the bonding surface. After that, a pressure sintering machine (IMC-1AB6 manufactured by Imoto Seisakusho) was used to pressurize at 5 MPa and sinter at 200° C. for 30 minutes in a nitrogen atmosphere to bond them. The bonding strength of the resulting bonded body was measured using an adhesive strength tester (Condor Sigma manufactured by XYZTEC).

[0268] The above measurement was performed three times, and the maximum value and average value of the bonding strength were calculated. They are shown in Table 3. In Table 3, the bonding strength is a value obtained by standardizing the bonding strength of Comparative Example 3 to 1.0. In Table 3, "-" means that it was not measured.

[0269]

[0270] As shown in Table 3, the conductive films of each example have low resistivity despite being manufactured by sintering at a relatively low temperature of 190°C. It is known that the copper powder used in each example has a low sintering temperature. In addition, it is also known that the conductive films of each example have good continuity and density due to excellent paste printability and low surface roughness Ra.

[0271] As is apparent from the comparison between Example 2 and Comparative Example 1, even when the same flat copper particles are used, when mechanically flattened copper particles such as copper particle B-3 are used, the sintering temperature of the copper powder increases and the resistivity of the conductive film also increases.

[0272] [Example 8, Comparative Example 8 and Comparative Example 9]

[0273] As shown in Table 4 below, when copper powder and polyethylene glycol having a number average molecular weight of 200 were mixed using a three-roll mill, the mixing ratio of copper powder to polyethylene glycol was changed to prepare a copper paste containing 90% by mass of copper powder. The same operation as in Example 2, Comparative Example 3, and Comparative Example 5 was performed to prepare copper pastes and conductive films of Example 8, Comparative Example 8, and Comparative Example 9. These copper pastes and conductive films were evaluated in the same manner as in Examples 1 to 7 and Comparative Examples 1 to 7. The results are shown in Table 4.

[0274] Table 4

[0275]

[0276] As shown in Table 4, the copper powders of Examples 2 and 8 containing both copper particles A-1 and B-1 are not easily adversely affected in the resistivity and surface roughness Ra of the conductive film even when the content of the organic solvent in the copper paste is changed. On the other hand, as shown in Comparative Examples 8 and 9, when using a copper powder containing only one of the copper particles A-1 and B-1, it is found that when the content of the organic solvent in the copper paste is set to 10 mass %, the resistivity of the conductive film in particular increases significantly.

[0277] Industrial Applicability

[0278] According to the present invention, a copper powder capable of producing a conductive film having high continuity and density and having a low sintering temperature can be provided.

Claims

1. A copper powder comprising the following copper particles A and copper particles B, wherein: The content ratio of copper particles A is 60 mass % or more and 99 mass % or less, and the content ratio of copper particles B is 1 mass % or more and 40 mass % or less, relative to the total of copper particles A and copper particles B. 〔Copper particles A〕 The copper particle includes a core particle containing copper and a coating layer covering a surface of the core particle. The covering layer is formed of a copper salt of an aliphatic organic acid, The primary particle size is 0.1 μm or more and 0.6 μm or less; 〔Copper particles B〕 For the copper particles, a ratio (S1 / B) of a first crystallite size S1 obtained by the Scherrer equation from the half-value width of a peak originating from the (111) plane of copper in X-ray diffraction measurement to a BET diameter B calculated from a BET specific surface area is 0.23 or less, The ratio (S1 / S2) of the first crystallite size S1 to the second crystallite size S2 obtained by the Scherrer equation from the half-value width of the peak derived from the (220) plane of copper in X-ray diffraction measurement is 1.35 or less. The primary particle size is 0.1 μm or more and 2.0 μm or less.

2. The copper powder according to claim 1, wherein The ratio (S1 / S3) of the first crystallite size S1 of the copper particle B to the third crystallite size S3 obtained by the Scherrer equation from the half-value width of the peak derived from the (311) plane of copper in X-ray diffraction measurement is 1.35 or less.

3. The copper powder according to claim 1, wherein The copper particles B contain carbon element, and the content of the carbon element is 5000 ppm or less.

4. The copper powder according to claim 1, wherein The copper particles B contain phosphorus, and the content of the phosphorus is 300 ppm or more. 5 . A copper paste comprising the copper powder according to claim 1 .

6. A method for manufacturing a conductive film, comprising: The copper paste according to claim 5 is applied on a substrate to form a coating film, and the coating film is fired.

Citation Information

Patent Citations

  • Copper powder

    JP2015168878A